2019
DOI: 10.3748/wjg.v25.i36.5483
|View full text |Cite
|
Sign up to set email alerts
|

CARMA3/NF-κB signaling contributes to tumorigenesis of hepatocellular carcinoma and is inhibited by sodium aescinate

Abstract: BACKGROUNDPrimary hepatocellular carcinoma (HCC) is a very malignant tumor in the world. CARMA3 plays an oncogenic role in the pathogenesis of various tumors. However, the function of CARMA3 in HCC has not been fully clarified.AIMTo study the biological function of CAEMA3 in HCC.METHODSTissue microarray slides including tissues form 100 HCC patients were applied to access the expression of CARMA3 in HCC and its clinical relevance. Knockdown and overexpression of CARMA3 were conducted with plasmid transfection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Moreover, CARMA3 promotes cell invasion and migration, and is positively correlated with lung cancer stemness, metastasis, and poor survival outcomes ( 54 ). Similar results have been observed in hepatocellular carcinoma ( 56 ), colorectal cancer ( 57 , 58 ), ovarian cancer ( 59 ), breast cancer ( 60 , 61 ), and renal cell carcinoma ( 62 64 ). In conclusion, CARMA3 is involved in the development and pathogenesis of various types of cancers.…”
Section: Carma3 In Cancerssupporting
confidence: 84%
“…Moreover, CARMA3 promotes cell invasion and migration, and is positively correlated with lung cancer stemness, metastasis, and poor survival outcomes ( 54 ). Similar results have been observed in hepatocellular carcinoma ( 56 ), colorectal cancer ( 57 , 58 ), ovarian cancer ( 59 ), breast cancer ( 60 , 61 ), and renal cell carcinoma ( 62 64 ). In conclusion, CARMA3 is involved in the development and pathogenesis of various types of cancers.…”
Section: Carma3 In Cancerssupporting
confidence: 84%
“…CARMA3 has been shown to be overexpressed in various human cancers [ 3 ]. Several studies reported that inhibition of CARMA3 decreased cell proliferation, migration, and tumor growth in NSCLC, bladder cancer, hepatocellular carcinoma, renal cell carcinoma, and colorectal cancer [ 4 , 5 , 6 , 7 , 8 ]. CARAM3 enhanced nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB) activation by regulating the downstream IKK complex activity in response to RTKs and PKC stimulation [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, particle size was rst analyzed by Design Expert 8.0.7 soware. The tting equation was described as following: PS ¼ 134.38 + 46.63A À 32.30B À 6.88C À 38.35AB + 12.26AC + 1.65BC + 26.68A 2 À 1.61B 2 + 11.18C 2 The results implied that the quadratic model was signicant. The P values of A, B, AB, and A 2 were all less than 0.05, suggesting that they had a considerable inuence on the PS of SLNs.…”
Section: Optimal Formulation Of Sa-slns-dementioning
confidence: 99%
“…Sodium aescinate (SA) is a triterpene saponin extracted from the dried fruits of Aesculus wilsonii Rehd . A number of studies have shown the therapeutic properties of SA, such as anti-inflammation, 1 anti-exudation, 2 detumescence, 3 and antioxidant effects; 4 it also can increase venous tension 5 and improve blood circulation. 6 …”
Section: Introductionmentioning
confidence: 99%